If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 5p = 2p + -5 Reorder the terms: 7 + 5p = -5 + 2p Solving 7 + 5p = -5 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 7 + 5p + -2p = -5 + 2p + -2p Combine like terms: 5p + -2p = 3p 7 + 3p = -5 + 2p + -2p Combine like terms: 2p + -2p = 0 7 + 3p = -5 + 0 7 + 3p = -5 Add '-7' to each side of the equation. 7 + -7 + 3p = -5 + -7 Combine like terms: 7 + -7 = 0 0 + 3p = -5 + -7 3p = -5 + -7 Combine like terms: -5 + -7 = -12 3p = -12 Divide each side by '3'. p = -4 Simplifying p = -4
| 4(6n+9)-10n=0 | | 67=7(7-6x)+3(x+6) | | x^2+22x-180=0 | | 6x+5=2x+13 | | 8x-8y= | | (2-4)+1=-11 | | 1+10x^2+x^4=0 | | 6(6t+3)=9(4t+2) | | 3(3-3x)=9 | | 4x+1=2x+9 | | -x^2+720x-14000=0 | | .25*x+[(2*x)*.05]=4.9 | | 7+8=.5(4*x-2) | | -3(3k-3)+3(1+3k)=12 | | 7x+17+5x=-31 | | -x^2+390x-27000=0 | | 4+14x^2-13x= | | 2(y^2-1)=3y | | 2x-24+24=86+24 | | -80=-8(3n-7)-2(n+3) | | m^3+26m^2+169m=0 | | 9w+1=7w-5 | | 15+(-5)+(-5)+15= | | -21+s=-30 | | 2(4-x)=10 | | 6-3*n=15 | | -21+x=5 | | -(a+4)-8(7-4a)=-29 | | 4+14x-13x= | | 7+m/8+1=-2 | | X-8X^4=0 | | -3x-4=53 |